Critical Analysis of the Election of the General Chairperson of the National Sports Committee of Provinces: A Democracy and Transparency Perspective - Murio, Akhiro; Widayati, Widayati (Jurnal Hukum Khaira Ummah, 2025)
This study aims to examine the regulations governing the Election of the General Chairperson in the National Sports Committee (KONI) Province. This issue is related to the election mechanism for the General Chairperson of the KONI Province from the perspective of democracy and transparency. This article also examines the ideal model for the election of the General Chairperson of the KONI Province from the perspective of democracy and transparency. The research method used in writing this article is a normative legal research type. Based on the results of the study, it can be concluded that the Election of the General Chairperson of the KONI Province according to Law Number 11 of 2022 concerning Sports, found shortcomings in the implementing regulations from the perspective of democracy and transparency. The ideal model for the election of the General Chairperson of the KONI Province from the perspective of democracy and transparency is that at the nomination stage the General Chairperson of the KONI Province must meet administrative requirements and pass a competency test, and at the election stage of the General Chairperson of the National Sports Committee Province, voting must be carried out even if there is only 1 (one) candidate for General Chairperson of the National Sports Committee Province.